PENERAPAN MODEL PROBLEM BASED LEARNING DALAM MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SDI WATU WANGKA, KECAMATAN PACAR - Eliterius Sennen; Restiana Nurtati; Sabina Ndiung (Jurnal Literasi Pendidikan Dasar (JLPD), 2022)
In learning activities in the classroom, the problems that are often faced by elementary school students are low mathematics learning outcomes. This study aims to explain the effect of the Problem Based Learning Learning model on the Mathematics learning outcomes of students at SDI Watu Wangka, Pacar District, West Manggarai Regency. This research is an experimental research using a quantitative approach. The population of this study were all students of SDI Watu Wangka, totaling 228 students, while the sample was 34 students of class IV. The sampling technique used was Purposive Sampling. The data analysis technique used statistical test using t-test. The results showed that the Problem-Based Learning model had a significant effect on the Mathematics learning outcomes of SDI Watu Wangka students. This can be seen from t0 > tα with a significant level of 0.05, which is obtained t0 = 2.12 and tα = 2.03 so that H0 is rejected or H1 is accepted. Thus it can be concluded that the application of the problem based learning model has a significant effect on the mathematics learning outcomes of SDI Watu Wangka students. That is, the mathematics learning outcomes of students who are taught using the problem based learning model are higher than the mathematics learning outcomes of students who are taught using conventional learning models.